Mali : Fifth Review Under the Poverty Reduction and Growth Facility. (IMF Staff Country Reports; Country Report ;, 2003)
This paper evaluates Mali's Fifth Review Under the Poverty Reduction and Growth Facility. The implementation of the program was satisfactory in the first nine months of 2002. All the quantitative performance criteria, benchmarks, and financial performance indicators were observed. The structural performance criteria and structural benchmarks for 2002 were met, except for one structural benchmark that was implemented late and an additional one that will be implemented in June 2003. The authorities intend to implement the ambitious medium-term economic framework and adjustment path underpinning the poverty reduction strategy adopted in May 2002.